The Berkeley-Illinois-Maryland-Association millimeter array - Welch, W; Thornton, D; Plambeck, R; Wright, M; Lugten, J; Urry, L; Fleming, M; Hoffman, W; Hudson, J; Lum, W; Forster, JR; Thatte, N; et al. (1996)
We describe the characteristics of the BIMA millimeter wave array at Hat Creek, CA. The array is an aperture synthesis instrument consisting of nine 6 m diameter antennas which may be deployed in three different configurations, with spacings ranging from 7 m up to 1.3 km. At an observing frequency of 100 GHz these configurations yield maps with angular resolutions of 5″, 2″, and 0.″4, over a 2′ field. Larger fields may be mapped by using multiple pointings. For all but the oldest telescopes, the surface accuracy is ≤30 μm rms, and the aperture efficiency is 77% at 100 GHz. Background emission from antenna losses and spillover is very low, about 5 K after subtraction of the cosmic B v(2.1 K). Each antenna contains a single dewar which accommodates up to four separate receivers. SIS mixers are cooled to 3.2 K with novel Gifford-McMahon cycle refrigerators. Both the upper and lower sidebands of the first local oscillator are received and separated, providing two bands extending from 70-900 MHz on each side of the first local oscillator. The correlation spectrometer covers a bandwidth of up to 800 MHz, and provides up to 2048 channels for each antenna pair. There are four independently tunable spectral windows (in each sideband), allowing simultaneous observations of several different spectral lines. The spectral resolution ranges from 6 kHz to 3 MHz. For a single 8-hr track in one configuration, the sensitivity is approximately 1 mJy/beam in the 800 MHz wide continuum. Measurements of atmospheric phase fluctuations as functions of both time and baseline have been made; these indicate that routine imaging at angular resolutions of less than 1″ at 100 GHz is possible only if self-calibration or some other means of phase correction can be applied. Examples of a few recent results are included. We note that 30% of the observing time on the array is granted to visitors.